2001
DOI: 10.1111/j.1745-6606.2001.tb00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Consumers Expect Companies to be Socially Responsible? The Impact of Corporate Social Responsibility on Buying Behavior

Abstract: Companies are facing increasing pressure to both maintain profitability and behave in socially responsible ways, yet researchers have provided little information on how corporate social responsibility impacts profitability. This paper reports the findings from in-depth interviews of consumers to determine their views concerning the social responsibilities of companies. A typology of consumers whose purchasing behavior ranges from unresponsive to highly responsive to corporate social responsibility was develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
1,141
1
81

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,555 publications
(1,255 citation statements)
references
References 33 publications
32
1,141
1
81
Order By: Relevance
“…Furthermore, purchasers are willing to be charged at higher price for products that meet corporate social responsibility's requirements and are friendly with the environment (Sempora, 2008;Seven One Media, 2009;DLG, 2010). The result in censuses and explorations showed that how much consumers are interested in corporate social responsibilities and how these responsibilities influence on purchasing of clients (Smith, 2009;Mohr et al (2001).…”
Section: Influences Of Corporate Social Responsibilities On Consumersmentioning
confidence: 99%
“…Furthermore, purchasers are willing to be charged at higher price for products that meet corporate social responsibility's requirements and are friendly with the environment (Sempora, 2008;Seven One Media, 2009;DLG, 2010). The result in censuses and explorations showed that how much consumers are interested in corporate social responsibilities and how these responsibilities influence on purchasing of clients (Smith, 2009;Mohr et al (2001).…”
Section: Influences Of Corporate Social Responsibilities On Consumersmentioning
confidence: 99%
“…First, while, previous researchers have developed consumer typologies based on general consumer expectations for firms to engage in socially responsible activities (Mohr et al 2001) and how consumers respond to specific CSR activities such as cause-related marketing campaigns (Webb and Mohr 1998), this current study is innovative as it explores the role of socially responsible consumption via gift-giving (i.e., buying for others). This in turn supports the development of a typology based on differences in personal consumption decisions and giftgiving decisions.…”
Section: "If I'm Buying a Gift For A Friend And I'm Trying To Impressmentioning
confidence: 99%
“…Second, socially responsible consumption behavior (SRCB), defined as "a person basing his or her acquisition, usage and disposition of products on a desire to minimize or eliminate any harmful effects and maximize the long-term beneficial impact on society" (Mohr et al 2001; 47) is rising in importance amongst consumers. However, previous research demonstrates that consumers who engage in some form of socially responsible consumption behavior do not necessarily behave uniformly.…”
Section: "If I'm Buying a Gift For A Friend And I'm Trying To Impressmentioning
confidence: 99%
See 2 more Smart Citations